Access to ınformation and social solidarity in the 2023 Turkey earthquake: disaster education as citizenship education - Jennifer Tupper; Ömer Cem Karacaoğlu (Humanities & Social Sciences Communications)
Abstract This qualitative study explores the experiences of 16 survivors of the 2023 earthquake in Turkey, aiming to highlight the critical role of disaster education within broader citizenship education. Through semi-structured interviews and inductive thematic analysis, four key themes emerged: access to information, trust in information sources, social solidarity, and the fulfillment of basic needs. These findings underscore the importance of integrating disaster education into citizenship education to empower individuals with the knowledge and skills necessary for effective disaster preparedness and response. The research advocates for multi-faceted approaches to disaster readiness that not only enhance immediate survival and recovery but also foster long-term community resilience. By amplifying the voices of earthquake survivors, this study contributes to a deeper understanding of the vital intersection between education, citizenship, and disaster management, offering insights into how to better equip citizens to respond to and recover from crises.